The influence of solvent on the pyrolysis of organosolv lignins extracted from willow. (January 2022) - Wang, Wenli; Liu, Yichen; Wang, Yue; Liu, Longfei; Hu, Changwei
Highlights: The oxygen containing functional groups in lignin varied with fractionation solvent. The decomposition temperature for the three lignins floated from 352 to 398℃. The pyrolysis of L-EAC and L-THF yielded guaiacol and 4-methylguaiacol dominantly. The pyrolysis of L-GBL yielded 4-methylguaiacol and 4-ethylguaiacol dominantly. Abstract: The targeted application of lignin needs deeper understanding of its physicochemical property. Herein, three kinds of organosolv lignin samples were obtained from willow using three typical organosolv-water co-solvents, and their properties and pyrolysis behaviors were studied by various characterization methods. It was found that the used solvents exerted different effects on lignin samples: lignin extracted from ethyl acetate-water co-solvent possessed more functional groups containing oxygen, and lignin extracted from γ-butyrolactone-water co-solvent contained more large-molecule fragments; the degradation temperature with the maximum rate in thermogravimetric analysis were 352, 384, and 398 ℃ for lignin samples extracted by ethyl acetate/tetrahydrofuran/γ-butyrolactone-water co-solvent, respectively. The cleavage of Cα -Cβ linkage performed more acutely in pyrolysis of lignin extracted from γ-butyrolactone-water co-solvent, while the linkage of C1 -Cα in lignin extracted by ethyl acetate/tetrahydrofuran-water co-solvent was more fragile. With regard to the mono-phenolic products, the pyrolysis of lignin extracted from ethyl acetate-water co-solvent yielded guaiacol and 4-methylguaiacol dominantly, and lignin extracted by tetrahydrofuran-water co-solvent produced more guaiacol, 4-ethylguaiacol, and 4-methylguaiacol while lignin extracted by γ-butyrolactone-water co-solvent yielded the maximum amount of 4-methylguaiacol. In addition, the pyrolysis of lignin samples extracted by γ-butyrolactone-water co-solvent yielded only H2, CH4 and CO as gaseous products while the other two yielded H2, CH4, CO and CO2 .